Collaboration of Parents and Care Professionals in Cases of Children Placed in Residential Care Homes - Parental Perspective - Jana Rapuš Pavel (Athens Institute for Education and Research, 2016)
The paradigm of residential child care, providing education and care for children outside the family is changing worldwide. The emphasis is shifting from a narrow child-focused approach to a more child-and-family centred one, foregrounding the quality of collaboration between parents and everyone involved in the child's care. Several Slovenian studies draw attention to the difficulties of maintaining a collaborative partnership with parents that is based on trust and contact. We introduce the findings of a qualitative research study that included 32 individuals with children in different residential care homes throughout Slovenia. The aim of the study was to analyze the experiences and needs of the parents that could contribute to a better collaboration with the care professionals. The findings show that the parents emphasized the following as important for good collaboration: communication and dialogue, being informed, included and accepted as an important part of the team.